2013
DOI: 10.1056/nejmoa1203366
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence during Cardiopulmonary Resuscitation

Abstract: Family presence during CPR was associated with positive results on psychological variables and did not interfere with medical efforts, increase stress in the health care team, or result in medicolegal conflicts. (Funded by Programme Hospitalier de Recherche Clinique 2008 of the French Ministry of Health; ClinicalTrials.gov number, NCT01009606.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
242
4
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(278 citation statements)
references
References 33 publications
8
242
4
24
Order By: Relevance
“…23 It is possible to check findings in literature that point convincingly the benefits of FCC in emergency assistance. For example, studies conducted in France showed that family members, when accompanying the cardiopulmonary resuscitation maneuvers had positive psychological outcomes and little negative interference in professional activities, 8 as well as lower frequency of complicated grief processes over a year. 24 So, it is important to discuss these issues with health professionals and managers to translate the available knowledge to clinical practice 25 and seek restructuring of services to facilitate the implementation of this type of care in the "UPA" in Brazil, in order to allow a development jump of assistance and test their viability for Brazilian culture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 It is possible to check findings in literature that point convincingly the benefits of FCC in emergency assistance. For example, studies conducted in France showed that family members, when accompanying the cardiopulmonary resuscitation maneuvers had positive psychological outcomes and little negative interference in professional activities, 8 as well as lower frequency of complicated grief processes over a year. 24 So, it is important to discuss these issues with health professionals and managers to translate the available knowledge to clinical practice 25 and seek restructuring of services to facilitate the implementation of this type of care in the "UPA" in Brazil, in order to allow a development jump of assistance and test their viability for Brazilian culture.…”
Section: Discussionmentioning
confidence: 99%
“…6 For the family, with these actions, it is enhanced the offer and receiving of information in a timely manner 7 and the reducing of chances of developing post-traumatic stress disorder in those who follow invasive procedures and cardiopulmonary resuscitation maneuvers. 8 Most of the scientific evidence and the reports of the implementation of the FCC is related to child health [4][5][6][7][8][9] and hospitalization scheme, 6 especially as a result of the planning and implementation of the FCC have being started in pediatric units. The recent consideration of the FCC for the adult and elderly population, particularly in critical situations and emergency, began with the increasing spread of the understanding that the family is the basic social interaction unit and, therefore, is the primary educator and support, regardless of the age of the patient and the local of provision of assistance, 5 making inconceivable the non-recognition of the familiar context in the treatment instituted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the evidence for its positive effects on patients' families continues to increase, the practice is still under debate and its implementation remains inconsistent. 102,103 Using a 63-item survey, Tudor et al 104 conducted a monocentric study among a convenience sample of 154 nurses working in both inpatient and outpatient units to explore their experiences with resuscitation, perceptions of benefits and risks of family presence, and self-confidence in family presence at the workplace. The latter was significantly related (P < .001) to the perceived benefits, and was significantly greater in participants who had completed an advanced training program, were highly experienced in resuscitation, specialty certified, or a member of a professional organization.…”
Section: Family Mattersmentioning
confidence: 99%